Valor Nutritivo de Dietas Contendo Sorgo, Milheto e Farelo do Mesocarpo de Babaçu em Substituição ao Milho em Ovinos. - Moura, Ludmilla Gomes Penha de (Universidade Federal do Tocantins, 2023)
The objective of this study was to evaluate the intake in sheep and apparent digestibility of diets containing sorghum, millet and babassu mesocarp meal (BMM) replacement for corn. We used 20 sheep housed in individual metabolic cages and distributed in a completely randomized design with four treatments (maize, millet, sorghum and BMM) and five replications, in which an analysis of variance was carried out to evaluate the effect of treatment, and the Student t test for comparison of the results. We collected samples of food, concentrated, leftovers and feces, used to determine the eating of nutrients and apparent digestibility. The dry matter intake (DMI), of organic matter (OMI), ether extract (EEI), non-fiber carbohydrates (CNFI) and total digestible nutrients (TDNI) were lower for animals fed diet with BMM in g/day ( 804.92, 750.48, 20.98, 343.84 and 537.98 respectively) and g/UTM (60.1693, 56.0805, 1.5689, 25.7987 and 40.1068 respectively); the consumption of crude protein (CP) was not influenced by the tested ones, whereas the consumption of fiber in neutral detergent (NDF) showed the highest values for animals fed diets with millet (383.40 g/day and 11.0244 in g/UTM). The digestibility of DM, OM and NDF were lower when the BMM replaced corn in the diet (0.6626, 0.6779 and 0.4004 respectively), for CP digestibility lower values were observed when we replaced corn by sorghum (0.6383) and digestibility of EE and NFC were lower when using millet instead of corn (0.3956 and 0.8694). The TDN was lower when we replaced corn by BMM (0.667) and afterwards by millet (0.7113). We conclude that millet and sorghum are good alternatives to replace corn and that more studies are needed to evaluate the replacement potential of babassu mesocarp meal by corn.